Gene X Environment Interactions and Pillow Talk: Investigating the Associations among the OXTR Gene, Orgasm, Post Sex Communication, and Relationship Satisfaction in Young Adult Relationships. Issue 1 (2nd January 2021) - Denes, Amanda
ABSTRACT: The present investigation tested the effects of a gene x environment interaction on sexual communication and relational well-being. It was hypothesized that the interaction of variation in oxytocin receptor gene OXTR rs53576 and orgasm would predict post sex communication and subsequent relationship satisfaction. The results revealed that for women in the sample, orgasm was positively associated with disclosing positive thoughts and feelings for one's partner after sexual activity, which in turn predicted greater relationship satisfaction, regardless of their genotype. The same model was supported for men with the GG genotype for OXTR rs53576, but not for those with the AA or AG genotypes, though the findings should be interpreted with caution due to the small percentage of men who did not orgasm. The findings and their implications for the post sex disclosures model and research on sexual communication are discussed.